Monitoramento do desgaste da ferramenta no processo de usinagem por torneamento através da potência - Assis, Diego Gomes de (Universidade Federal Rural do Semi-Árido, 2019)
During the machining process, the most important component, as well as other manufacturing processes, is the part, and the factor that most influences its manufacture is the tool. So, a special attention should therefore be paid to this component, because depending on the type of material or even the time process, because depending on the type of material or even the process time, its wear is accentuated, becoming a problem. The goal of this work is the monitoring of the wear of the high speed steel tool for in the turning machining process, through an experimental apparatus assembled to measure the tool wear, checking the power consumed by the machine during the process. aiming to reduce downtimes and making the most efficient use of the tool in machining, maximizing the process. Were used five high speed steel tools, sharpening α = 8 °, β = 62 ° and γ = 20 °, machining ABNT 1045 Steel, using a cutting speed of 15m / min, an initial rotation of 118rpm, compensating when necessary, and the stopping criterion was the average flank wear value of 0.30mm according to ISO 3685, measured with a low resolution optical microscope. Current measurements were made using a clamp meter model ET-4090 with a resolution of up to two decimal places for the measured currents. Useful life curve graphs were included at this work for each tool and an average of statistics among them, thus generating a confidence interval for the measurements which were tested with three tools to validate the system. For this validations, the power consumed by the equipment was established as a stopping criterion, specifically using the current parameter. The values measured at validation were statistically equal to the confidence interval values showing a valid result for the wear curve with respect to power.
Monografia
Keywords: Torneamento; Potência; Vida-Útil; Monitoramento; Desgaste; ENGENHARIAS::ENGENHARIA MECANICA